Attention‐deficit hyperactivity symptoms and risk of alcohol use relapse. Issue 1 (26th December 2022) - Kawata, Takahiro; Sugihara, Genichi; Kakibuchi, Yoichi; Tomitaka, Midori; Miyajima, Miho; Matsushima, Eisuke; Takeuchi, Takashi; Takahashi, Hidehiko
Abstract: Aim: Alcohol use disorder (AUD) is frequently accompanied by comorbid attention‐deficit hyperactivity disorder (ADHD). Comorbid ADHD has been reported to increase the severity of AUD. We investigated whether ADHD severity also influences AUD relapse risk at baseline and after inpatient treatment. Methods: In this study, 187 AUD patients admitted to Narimasu Kosei Hospital from October 2019 to March 2021 were included in the analysis. According to the Adult ADHD Self‐Report Scale (ASRS), participants were divided into two groups: ASRS+ with ADHD characteristics ( n  = 43) and ASRS− with low/no ADHD characteristics ( n  = 144). Groups were compared for AUD relapse risk at the start of treatment (baseline) and before hospital discharge using the multidimensional Alcohol Relapse Risk Scale (ARRS). The change in relapse risk during hospitalization was also compared by assessment of the interaction between groups (ASRS+ vs. ASRS−) and time (at discharge vs. baseline). Results: The total ARRS score and dimension subscores for stimulus‐induced vulnerability and emotionality problems were significantly higher in the ASRS+ group at baseline and before discharge compared to the ASRS− group. There was a significant group × time interaction indicating less improvement of stimulus‐induced vulnerability during inpatient treatment among the ASRS+ group compared to the ASRS− group. Conclusions: Our findings suggest that AUD patients with ADHD characteristics have a higher risk of relapse both at baseline and after inpatient treatment. Stimulus‐induced vulnerability to relapse is less likely to improve with treatment in patients with ADHD characteristics. Abstract : According to the Adult ADHD Self‐Report Scale (ASRS), alcohol use disorder (AUD) inpatients were divided into two groups, ASRS+ with ADHD characteristics ( n  = 43) and ASRS− with low/no ADHD characteristics ( n  = 144). Groups were compared for AUD relapse risk at baseline (BL) and before discharge (BD) using the multidimensional Alcohol Relapse Risk Scale (ARRS), and the change in relapse risk during hospitalization was also compared by assessment of the interaction between groups (ASRS+ vs. ASRS−) and time (BL vs. BD). AUD patients with strong ADHD characteristics were at higher risk of relapse at baseline and following inpatient treatment due to persistent stimulus‐induced vulnerability.